Microcontrollers high-performance systems and programming - Sanchez, Julio 1938-; Canton, Maria P. (CRC Press, 2014)
"This book focuses on high-performance microcontrollers and on the digital signal processors offered by Microchip. In addition to their enhanced features, extended peripherals, and improved performance, there are several practical factors that make the high-performance PIC series a better choice than their mid-range predecessors for most systems: The possibility of programming high-performance microcontrollers in a high-level language (C language)Source code compatibility with PIC16 microcontrollers, which facilitates code migration from mid-range to PIC18 devicesPin compatibility of some PIC18 devices with their PIC16 predecessors. This makes possible the reuse of PIC16 controllers in circuits originally designed for mid-range hardware. One consideration that is sometimes mentioned in favor of the mid-range devices is the abundance of published application circuits and code samples. This book attempts to correct this. It is a continuation of Embedded Systems Circuits and Programming (CRC Press, 2012) by the same authors"--Provided by publisher.